2016
DOI: 10.7243/2054-992x-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between autism and glyphosate-formulated herbicides?

Abstract: Glyphosate is the most widely used herbicide on the planet, and its increasing use over time in the United States aligns well with the increasing rates of autism determined by the Centers for Disease Control. Based on the known mechanism of glyphosate toxicity, we hypothesize that a pregnant woman's exposure at midpregnancy to glyphosate-formulated herbicides (GFH) may produce, in her unborn child's brain, anatomic alterations of cortical neuron layering remarkably similar to those found in the brains of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 70 publications
0
9
0
2
Order By: Relevance
“…They extend this reasoning to multiple body functions to propose that the dysregulation of Mn utilization in the body due to glyphosate’s metal chelating properties explains autism, Alzheimer’s disease, Parkinson’s disease, anxiety disorder, osteoporosis, inflammatory bowel disease, renal lithiasis, osteomalacia, cholestasis, thyroid dysfunction, and infertility. More recently, Beecham and Seneff have used the same reasoning to conclude on a causative link between glyphosate chelation of Mn and the large rise in the incidence of autism spectrum disorders in children within the US ( 35 ). However, there are no scientific studies establishing a causative link between glyphosate and the described chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…They extend this reasoning to multiple body functions to propose that the dysregulation of Mn utilization in the body due to glyphosate’s metal chelating properties explains autism, Alzheimer’s disease, Parkinson’s disease, anxiety disorder, osteoporosis, inflammatory bowel disease, renal lithiasis, osteomalacia, cholestasis, thyroid dysfunction, and infertility. More recently, Beecham and Seneff have used the same reasoning to conclude on a causative link between glyphosate chelation of Mn and the large rise in the incidence of autism spectrum disorders in children within the US ( 35 ). However, there are no scientific studies establishing a causative link between glyphosate and the described chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of GBHs on human health are under intense public debate, evidence is emerging that they impact many health outcomes, including developmental and reproductive toxicity [36][37][38] , endocrine disruption 39,40 , host immunity [41][42][43] , obesity and diabetes 7,44 , gastrointestinal disorders 45 , cardiovascular disorders 46,47 and central nervous system dysfunction such as learning and memory impairment 48 , anxiety, depression 49 and autism 8 . These chronic health outcomes may occur even at doses lower than established risk safety guidelines, in particular during critical development windows as denoted in the DOHaD paradigm 50 .Environmental exposures may lead to changes in metabolism 18,51 .…”
Section: Discussionmentioning
confidence: 99%
“…However, current emerging evidence suggest that glyphosate or GBH such as Roundup, can adversely affect mammalian biology via multiple mechanisms [5][6][7][8] . Several studies have also suggested the possible link between GBHs exposure and abnormality in neurodevelopment 55,56 .…”
Section: Introductionmentioning
confidence: 99%
“…22,24 Furthermore, the increased use of the glyphosateformulated herbicide has also been associated with the increase in autism prevalence via its influence of the thyroid-stimulating hormone of pregnant women. 25…”
Section: Pollutionmentioning
confidence: 99%